GERMANY IS AHEAD TO IMPLEMENT SUSTAINABLE CIRCULAR ECONOMY - Mohajan, Haradhan Kumar (Journal of Economic Development, Environment and People, 2021)
This study tries to discuss aspects of application of circular economy (CE) in Germany. Since the start of the First Industrial Revolution (start in 1760), more than 260 years ago, there becomes enormous development in global linear economy (LE) on the basis of ‘take, make and dispose’. Modern various technologies, such as automobiles, electricity, telephones, mobile phones, transistors, airplanes, computers, and the internet have brought enormous change in production and consumption. But unsustainable side effects of LE are; loss of biodiversity, deforestation, environment pollution, climate change, etc. On the other hand, CE represents a sustainable economy. It keeps resources and materials, as long as, possible. The purpose of this study is to show the importance and beneficial effects of a realized CE on the economic, environmental and social sectors for the success of global sustainable development and the contribution of CE in Germany. Germany is the first country in the world that tries to implement CE by using technologies of waste and resource management.